2004
DOI: 10.1074/jbc.408842200
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of Cells to TRAIL-induced Apoptosis by Decoy Receptor 3

Abstract: Decoy receptor 3 (DcR3)/TR6/M68 is a soluble receptor that binds to the Fas ligand LIGHT and TL1A. Elevated levels of DcR3 expression have been found in many tumors. We report an unexpected effect of DcR3 by sensitizing Jurkat and U937 cells to apoptosis induced by tumor necrosis factor-related apoptosis-inducing ligand (TRAIL). Cell death triggered by anti-Fas and tumor necrosis factor was unaffected by DcR3. DcR3 by itself did not stimulate apoptosis. The ability to augment TRAIL-initiated cell death was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Even though TRAIL is considered an important therapeutic agent for tumor treatment, clinical trials have revealed its limitations due to the acquisition of tumor resistance. There are lots of mechanisms by which tumor cells acquire TRAIL resistance, such as induction of decoy receptors (DcR1 and DcR2), 29,33 anti-apoptotic proteins (c-FLIP, IAPs, Bcl2, Bcl-xL, and Mcl-1), 34−36 and proliferation activators (PI3K, AKT, and NF-κB). 37−39 Another major strategy to induce TRAIL resistance is to suppress death receptors DR5 and/or DR4.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Even though TRAIL is considered an important therapeutic agent for tumor treatment, clinical trials have revealed its limitations due to the acquisition of tumor resistance. There are lots of mechanisms by which tumor cells acquire TRAIL resistance, such as induction of decoy receptors (DcR1 and DcR2), 29,33 anti-apoptotic proteins (c-FLIP, IAPs, Bcl2, Bcl-xL, and Mcl-1), 34−36 and proliferation activators (PI3K, AKT, and NF-κB). 37−39 Another major strategy to induce TRAIL resistance is to suppress death receptors DR5 and/or DR4.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It has been reported that several genes increased the sensitivity to TRAIL via activating pro‐apoptotic factors or suppressing anti‐apoptotic factors. For example, (i) adenoviral vector expressing CYLD increased the sensitivity to TRAIL by suppression of NF‐κB survival signaling in hepatocellular carcinoma [Chu et al, 2006]; (ii) somatostatin receptor subtype 2 (sst2) up‐regulated expression of DR4 and TNFRI, sensitizing the cells to death ligand‐induced initiator capase‐8 activation, as well as down‐regulated expression of the antiapoptotic mitochondrial Bcl‐2 protein [Guillermet et al, 2003]; (iii) decoy receptor 3 (DcR3) increased TRAIL‐induced caspase‐8 activation and Bid cleavage, enhanced Smac release from mitochondria, and augmented caspases‐3 and ‐9 activation [Wu et al, 2004]; (iv) overexpression of reticulon 3 (RTN3) enhances TRAIL‐mediated apoptosis via up‐regulation of death receptor 5 (DR5) and down‐regulation of c‐FLIP [Lee et al, 2009]; (v) prostate apoptosis response gene‐4 (par‐4) enhances sensitivity towards TRAIL by an enforced cleavage of c‐FLIP L together with an increased activation of the initiator caspases‐8 and ‐10 and expression of par‐4 enables cells to down‐regulate the inhibitor‐of‐apoptosis proteins c‐IAP‐1, c‐IAP‐2, XIAP, and survivin [Boehrer et al, 2006]. However, Boehrer et al reported that Par‐4 promotes apoptosis induced by TRAIL through activation of caspase‐dependent pathway, its sensitizing mechanism was not determined.…”
mentioning
confidence: 99%
“…DcR3 enhances apoptosis in TRAIL-sensitive transformed T-cells without triggering any apoptotic event ( 28 ). TRAIL and FasL, which play major roles in allograft rejection ( 13 , 29 ), were detected in T-cells co-cultured with BMDCs using western blot ( Supplementary Figure S7 ).…”
Section: Resultsmentioning
confidence: 99%